Control of protein synthesis in Semliki forest virus-infected cells. - Lachmi, B (1977)
Protein synthesis in Semliki forest virus-infected chicken embryo cells was studied by labeling them with [35S]methionine for short periods at different times after infection, with or without synchronization of protein synthesis by the hypertonic block technique. The rate of host-cell protein synthesis declined almost linearly in inverse correlation to the increase in the amount of virus specific RNA. At 5.5 h postinfection, the host-cell protein synthesis was reduced by about 70%. The viral structural proteins were detectable with certainty at 3.5 h postinfection, and their rate of synthesis increased linearly parallel to the amount of their messenger, the 26S RNA. This suggests that the rate of synthesis of the structural proteins is controlled at the level of transcription. The rate of synthesis of the virus-specific nonstructural proteins attained its maximum between 3 and 4 h postinfection and declined thereafter, wheras the amount of their messenger, the 42S RNA, continued to increase linearly in the cells. Thus, the messenger activity of the 42S RNA is reduced in the late phase of infection compared with its activity in the early phase.